Physical Education in High School: The Contribution of Noble Values in Sports - Henri Saputra; Eri Barlian; Padli Padli; Bayu Iswana (Journal of Coaching and Sports Science, 2022)
Instillingnoble values in sports at school, especially physical education subjects, is not optimal at the high school level because of its unstable nature. The problem in research is that many students still do not have a sportsmanlike attitude when they accept defeat. Besides, they do not have a sense of responsibility and discipline in the group during practical subjects. The purpose of this study was to determine the contribution of the noble values of sports to the attitude of responsibility and discipline. This study uses a quantitative method which is quantitative with a regression test. The population and the sample are 60 random students. In calculating the regression coefficient, the value is positive, and the result of the equation in the constant is 22.191, which means that the consistency value is 22.191. With a contribution of 17.00 percent. This study concludes that the noble value in sports on affective responsibility and discipline shows an outstanding category.